Dać pokój ziemi. Egzegeza wybranych tekstów Nowego Testamentu - Kiersztejn, Joanna (Humaniora. Czasopismo Internetowe, 2024)
The peace in the Bible is a virtue connected to God himself. Analysing the New Testament’s writings, we discover that the peace brought by Christ cannot be read and understood only from political perspective thus it is not just a simple lack of war. The peace is God’s gift, it is the sign of the time of the Messiah. In Paul’s letters the peace it is a virtue related to justification that must be cultivated, because the peace of God is more effective than a man can imagine. It can not only break down all hostility and divisions, but also bring men closer to God himself. The John’s tradition brings similar view. Peace as a reality related to Jesus himself is the fullness of messianic goods and is eschatological in nature. However, these features make it therefore unfamiliar to the world. Adopting this way of seeing the peace and then putting it into practice has also its consequences. It leads to breaking away from the ‘structure of the world’ as we know it. But only then peacemaking becomes a manifestation of true wisdom. All those who introduce peace understood in this way deserve to be called children of God.